Genetic diversity of Plasmodium falciparum merozoite surface protein‐1 (block 2), glutamate‐rich protein and sexual stage antigen Pfs25 from Chandigarh, North India. Issue 12 (9th November 2017) - Kaur, Hargobinder; Sehgal, Rakesh; Goyal, Kapil; Makkar, Nikita; Yadav, Richa; Bharti, Praveen K.; Singh, Neeru; Sarmah, Nilanju P.; Mohapatra, Pradyumna K.; Mahanta, Jagadish; Bansal, Devendra; Sultan, Ali A.; et al.
Abstract: Objective: To elucidate the genetic diversity of Plasmodium falciparum in residual transmission foci of northern India. Methods: Clinically suspected patients with malaria were screened for malaria infection by microscopy. 48 P. falciparum ‐infected patients were enrolled from tertiary care hospital in Chandigarh, India. Blood samples were collected from enrolled patients, genomic DNA extraction and nested PCR was performed for further species confirmation. Sanger sequencing was carried out using block 2 region of msp1, R2 region of glurp and pfs25 ‐specific primers. Results: Extensive diversity was found in msp1 alleles with predominantly RO33 alleles. Overall allelic prevalence was 55.8% for RO33, 39.5% for MAD20 and 4.7% for K1. Six variants were observed in MAD20, whereas no variant was found in RO33 and K1 alleles. A phylogenetic analysis of RO33 alleles indicated more similarity to South African isolates, whereas MAD20 alleles showed similarity with South‐East Asian isolates. In glurp, extensive variation was observed with eleven different alleles based on the AAU repeats. However, pfs25 showed less diversity and was the most stable among the targeted genes. Conclusion: Our findings document the genetic diversity among circulating strains of P. falciparum in an area of India with low malaria transmission and could have implications for control strategies to reach the national goal of malaria elimination.